Laboratory Safety, Biosecurity, and Responsible Animal Use. (16th August 2019) - McCormick-Ell, Jessica; Connell, Nancy
Abstract: Research with animals presents a wide array of hazards, some of which overlap those in the in vitro research laboratory. The challenge for environmental health and safety professionals when making their recommendations and performing the risk assessment is to balance worker safety with animal safety/welfare. The care and husbandry of animals require procedures and tasks that create aerosols and involve metabolized chemicals and a variety of physical hazards that must be assessed in addition to the research related risks, all while balancing the biosecurity of the facility and NIH animal care requirements. Detailed communication between health and safety, research, and animal care teams is essential to understand how to mitigate the risks that are present and if modifications need to be made as the experiments and processes progress and change over time. Additionally, the backgrounds and education levels of the persons involved in animal research and husbandry can be quite broad; the training programs created need to reflect this. Active learning and hands-on training are extremely beneficial for all staff involved in this field. Certain areas of research, such as infectious disease research in high- and maximum-containment (biosafety level 3 and 4) facilities, present challenges that are not seen in lower containment or chemical exposure experiments. This paper reviews potential hazards and mitigation strategies and discusses unique challenges for safety at all biosafety levels.